Golden arches east: McDonald´s in east Asia - Watson, James L.
Golden Arches East: McDonalds in East Asia is an absorbing read that delves into more than just eating; it grapples with the big issues like the impact of local vis-à-vis the global by looking into the interplay of McDonald?s in five Asian economies. Watson, et al concludes that in several spaces - particularly in Asia - McDonald?s amalgamated into the local communities. McDonalds has integrated so well that the distinction between local and foreign has blurred. So disentangled is the distinction that McDonalds is no longer considered a foreign restaurant and arguably in many cases - such as the ones explored in this book - no longer functions as one. This is an essential book because it accurately portrays and cognizant of local nuance how a transnational culture is developing. Golden Arches East: McDonalds in East Asia is a necessary read for anyone interested in globalization. At a time when academics frequently write impenetrably this book is a breath of fresh air. Golden Arches is very engaging and is deals with one straightforward question: how do countries act in response to McDonald?s, and conversely what does the relation say about those countries? The inquiry is not petty. The book is an exploration of McDonald?s in Hong Kong, Beijing, Taipei, Seoul and Tokyo. Undoubtedly, McDonald?s has had a huge effect in Asia, influencing manners and values and the way people interact. The most informative part of these studies is its exploration of how McDonald?s changed each country. While Americans might see themselves as the bright light of global democracy and human rights, its impact in countries in East Asia is proving to be more empirical. Bathrooms in Hong Kong restaurants, according to this study had undergone a tremendous transformation. Riding into town with the McDonalds penchant for cleanliness, the other restaurants seem to have followed suit. It might seem like an exaggeration but Watson et al credits McDonald?s for assisting in elevating the cleanliness and safety standard in public rest rooms in Hong Kong. Another thing that is happening in Hong Kong is the ?disciplining? of the users. According to Watson et al the carceral community takes care of its own. Self-reflective of exaggerating McDonalds impact in the milieu, Watson et al claim that even if McDonalds did not indeed take the active role in creating a form of queuing discipline - it?s perceived to have done so. Moving onto the perhaps the marquis section of the book, Japan?s values have been changing for decades, becoming steadily more casual, and according to Watson et al McDonald?s may be assisting as vehicle in that process. This proves at least one thing - that there is nothing primordial or essential about cultures but that culture and societies change, reinvent themselves, and reify their existence by the re-enforcement and performance or cultural play. To the chagrin of conservatives, this is reality. According to Emiko Ohnuki-Tierney, Japan has a long-standing taboo against ?tachigui,? (standing while eating) but that seems to be steadily breaking down. Ohnuki-Tierney suggests that perhaps the catalyst of this change is McDonald?s - whose stores in Japan just did not accommodate sitting - there were no chairs. In Beijing, restaurants where known for their noise and dirt. However, according to Watson et al, customers at McDonald?s branches in Beijing spoke in hushed tones and were cognizant of the changing conditions regarding spitting and rubbish. All this might look like American cultural imperialism - as is examined in the section on Seoul. However, it is difficult to conceive of even the most zealous anti-American in East Asia disapproving of American exports like efficiency, smiles and clean rest rooms. The real potency of Golden Arches East: McDonalds in East Asia is that the writers place in context not just the food side of McDonald?s, but also more importantly the social and cultural impact of McDonalds on these ever-changing societies. These are loaded tales of the mundane and everyday. In short, this rare academic engagement should reside in all libraries and spawn similar studies.